(untitled) (المجلة الدولية للبحوث العلمية, 2026)
This research aims to study the importance of scientific evaluation of members of general assemblies and sports committees, and how the scientific qualifications of members affect the improvement of institutional performance in sports institutions. The research deals with the concept of scientific evaluation and its applications in sports management, with a focus on developing strategic planning, raising the level of professionalism in decision-making, and improving administrative performance. The research also reviews some of the challenges facing the application of scientific evaluation, such as lack of resources and resistance to change, and proposes possible solutions to overcome these challenges through Cooperating with universities, developing continuous training programs, and promoting an institutional culture that supports science.